Anti-Inflammatory Activity of Gallic Acid by Suppression of Cyclooxygenase, Lipoxygenase and Nitric Oxide - Veerichetty, Veerabhuvaneshwari; Nachimuthu, Saraswathy (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Gallic acid, trihydroxy benzoic acid is a phenolic compound abundant in various fruits and plants with potent antioxidant and anti-inflammatory properties. This study aims to investigate dual COX LOX inhibition in silico and in vitro to exhibit safer anti-inflammatory potential sparing gastrointestinal toxicity observed with selective COX inhibitors. Materials and Methods: Anti-inflammatory activity of gallic acid was evaluated in vitro by measuring cyclooxygenase, lipoxygenase, and nitric oxide activity and gene expression in RAW macrophage cells. In silico molecular docking and simulation was performed for gallic acid and diclofenac standard against cyclooxygenase and lipoxygenase. Results: Gallic showed inhibition of cyclooxygenase and lipoxygenase with an IC50 of 38.94 μg/mL and 17.85 μg/mL against diclofenac standard with a 34.93 μg/mL and 26.54, 18.58 μg/mL. Gallic acid also reduced nitric oxide production in raw macrophages with an IC50 of 22.96 μg/mL against diclofenac showing μg/mL. Gallic acid suppressed expression of iNOS, COX2 and LOX mRNA in RAW 264.7 macrophages. Gallic acid showed in silico binding energy of -6 kcal/mol and -6.30 kcal/mol against cyclooxygenase and lipoxygenase. Diclofenac showed in silico binding energy of -7.21 and -7.53 kcal/mol against cyclooxygenase and lipoxygenase. Binding modes and molecular dynamics simulation analysis of gallic acid and diclofenac were studied in cyclooxygenase and lipoxygenase active site pockets. Conclusion: Gallic acid exerts its anti-inflammatory potential without shunting arachidonic acid pathway and can be used in place non-steroidal and steroidal anti-inflammatory drugs. Hence, our studies reinforce that gallic acid act through COX-2/5-LOX pathway sparing mucosal damage and effective for chronic inflammatory diseases.
Keywords: Gallic acid; Diclofenac; Cyclooxygenase; Lipoxygenase; Nitric oxide; iNOS; Anti-inflammatory